Psychological Trauma as a Severe and Lasting Consequence of Sexual Abuse - Riska Rahmasari; Matang (Journal of Science and Research, 2025)
Sexual harassment is a form of violence that not only causes physical injury but also has profound psychological consequences for victims. The impacts of sexual violence may include depression, phobias, nightmares, and long-term distrust toward others. The purpose of this study is to describe the forms of psychological trauma experienced by survivors of sexual harassment and the adaptation processes they undergo in their daily lives. This study employs a qualitative descriptive method, with data collected through in-depth interviews with three informants who are survivors of sexual harassment. The findings reveal that the victims experience various forms of psychological trauma, including Post-Traumatic Stress Disorder (PTSD), a drastic decline in self-confidence, sleep disturbances, and persistent negative thoughts. In addition, social impacts also emerged, such as withdrawal from social interactions and heightened suspicion toward the opposite sex. Therefore, adequate psychological support, social rehabilitation, and the creation of a safe and supportive environment are essential to help survivors begin their recovery process and regain their quality of life.